Effect of Cirripedia sp. Flour As Subtitutional Feed Source of Protein Against Dried Disease and Organic Material Rabbit Rain Type Rex - Bodhi Agustono; Widya Paramita Lokapirnasari; Mohammad Anam Al Arif; Ragil Angga Prastiya; Faisal Fikri (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2020)
The aim of this research was to determine the effect of Cirripedia sp. flour as feed substitution of protein source in feed on the digestibility of dry matter and organic matter in 100 male rex broilers. The research was experimental by using a completely randomized design with four treatments and five replications. Substitution of Cirripedia sp. flour respectively in feed were 0%, 2.5%, 5%, 7.5% given for four weeks. Data collection was carried out in the fourth week (for seven days) which included consumption data, manure weight and analysis of treatment feed and manure analysis. The data were analyzed using Analysis of Variance and the difference between treatments was determined by the Duncan test. The results showed that there was no significant difference (p>0.05) and that there was no significant difference (p>0.05) on the digestibility of rex broilers. This shows that the substitution of Cirripedia sp. flour in feed can replace animal protein sources in fish meal in complete feed rabbits.Key words : Cirripedia sp, digestibility, feed subtitution, flour, rabbit.